Role of MicroRNAs in Zygotic Genome Activation: Modulation of mRNA During Embryogenesis. - Rosa, A.; Brivanlou, A.H. (Methods in molecular biology (Clifton, N.J.), 2017)
A fundamental process occurring during early development is the zygotic genome activation, i.e., the initiation of transcription from the embryonic genome. Before that step, cellular processes in the developing embryo are dictated by transcripts produced by the maternal genome and accumulated in the egg during oogenesis. The maternal-to-zygotic transition (MZT) involves both the clearance of maternal RNAs and the initiation of transcription of the embryonic genome and is a tightly regulated process. In some species, decay of maternal transcripts may be facilitated by the activity of microRNAs. These small RNAs can act pleiotropically, blocking translation and inducing destabilization of hundreds of different maternal targets. In this review, we will discuss the role of microRNAs during MZT, focusing on Drosophila melanogaster and vertebrate models, Xenopus laevis, Zebrafish and mouse, in which such a mechanism has been more extensively studied.